The design of secure mobile coupon mechanism with the implementation for NFC smartphones. (April 2017) - Chen, Yu-Yi; Tsai, Meng-Lin; Chang, Fong-Jia
Highlights: This study describes the design and implement a secure mobile coupon system for NFC smartphones. The proposed protocol guarantees non-repudiation, integrity, and anti-counterfeit of loyalty points and m-coupons. The prototype system focuses on the process of loyalty points earning, the m-coupon redemption, and the m-coupon using. Abstract: Due to the rise of mobile commerce, companies start issuing more mobile coupons (m-coupons) for mobile users. With Near Field Communication enabled (NFC-enabled) smartphones, customers could now receive their m-coupons anytime anywhere and use them with ease. In this paper, we design and implement a secure mobile coupon system for NFC smartphones. The prototype m-coupon system focuses on the process of loyalty points earning, the m-coupon redemption, and the m-coupon using. Our design guarantees non-repudiation, integrity, and anti-counterfeit of loyalty points and m-coupons. This scheme can be practically applied to m-coupon campaigns and meet security requirements in the mobile environment. Graphical abstract: